RESEARCH TRAINING OF STUDENTS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS BASED ON THE CONTENT AND STRUCTURE OF A MODERN ENGINEER’S RESEARCH ACTIVITY - Gorshkova Оksana (Revista Inclusiones, 2020)
The urgency of the problem under investigation is due to the transition to an innovative economy, the development of information technologies, the creation and spreading of complex human-machine systems, of sociotechnics, which has qualitatively changed the engineering activity, made it allencompassing, the driving force behind the technological transformation of society. Worldwide, there is a growing need for competitive engineering personnel ready for active participation in innovative engineering processes, the development of new ideas, the solution of research production problems – in other words, for professionals who do not think in a conventional way and are capable of adopting non-standard solutions exhibiting research behavior, since the engineer of the future is a research engineer. The purpose of the article is to solve the problem of research training in the context of competence-oriented engineering education on the basis of the content and structure of research activities of a modern engineer. Based on the systematization, analysis and development of existing provisions of scientific research and works in the field of engineering education, professional pedagogy and the specifics of engineering activities, on regulatory documents, educational and professional standards, the content and structure of the research activity of a modern engineer is defined. These provisions are the basis for a model aimed at research training of students of technical universities. Empirical methods (observation, questionnaires, interviews, testing, self-assessment, documentation analysis, product research, pedagogical design) made it possible to determine the level of research competence of first-year students and graduates before and after the experiment on implementing the model of student research.